Electrocardiogram assessment using the Einthoven and base-apex lead systems in healthy Holstein cows and neonates - Cedeno, Dario A.; Lourenço, Maria L.G. [UNESP]; Daza, Carmen A.B. [UNESP]; Filho, Plinio Pagnani [UNESP]; Chiacchio, Simone B. [UNESP] (FapUNIFESP (SciELO), 2016)
The objective aimed to describe the electrocardiographic behavior of parameters in Holstein pregnant cows and neonates during the perinatal period. The electrocardiograms were performed using a computerized electrocardiogram. The animals selected for the study were 23 cows and 18 neonates. Maternal electrocardiographic examinations were conducted in the 35, 28, 21, 14, 7 days and one-day pre -partum and the neonates were evaluated in six moments; at the time of birth, 7, 14, 21, 28 and 35 days after delivery. The evaluations were done in pre and post-delivery cows and into the group of neonates between female and male. For each electrocardiographic recording P-wave duration and amplitude, PR interval and the QRS complex duration, R, S-wave amplitude and polarity, QT and RR interval duration were examined. Changes in heart rate, ST segment and T wave polarity were recorded in leads of Einthoven and base-apex planes. The mean electrical axis of the QRS complex was calculated. In cows the results when comparing the two leads system, there are significant changes in the amplitude of the waves P, R, S, and T and the duration of the intervals PR, ST and QRS complex. The difference between primiparous and multiparous dairy cows was in the amplitude of the Twave. It was concluded that the base-apex system is a suitable lead for monitoring heart rhythm in Holstein cows and Einthoven in neonates. During the first month of life, no differences in P, Q, S and T waves, in PR, QRS, and ST intervals and in axis orientation was observed in neonates. There was a significant difference in duration of the QT interval. Among sexes, the difference was in the Q amplitude. This study incorporated the calves and Holstein cows in a single study in search of baseline information regarding the duration and morphology of the ECG parameters. In conclusion, it was proved that, with increasing age, there are changes in ECG components associated with variations in the distance between the recording electrode and the heart. The study contributes by providing Holstein reference values for clinical evaluations.
Keywords: Cattle; ECG components; Heart rate; Neonatology